Principles and Design Strategies for Ultra‐efficient Production Systems in the Process Industry. Issue 11 (1st September 2021) - Schutzbach, Maximilian; Full, Johannes; Kiemel, Steffen; Waltersmann, Lara; Sielaff, Lennard; Miehe, Robert; Sauer, Alexander
Abstract: A sustainable design of production systems, both within and beyond company boundaries, is essential for the future viability of the process industry. In this context, the concept of ultra‐efficiency has recently been developed, aiming at achieving holistic improvements in the fields of action energy and material efficiency, emission reduction, organization, human and staff, with the goal of establishing a positive impact factory. In this paper, the concept developed mainly for the discrete manufacturing industry is transferred to the process industry. It is put into the scientific sub context and elementary approaches, methods and strategies for factory planning and design of production processes in the process industry are summarized. Abstract : In order to introduce the concept of ultra‐efficiency from the discrete manufacturing industry to the process industry, we present a definition of the concept in differentiation to other approaches in this paper. Further, selected design strategies and methods for implementation in sustainable companies/company networks are described in detail.